Advanced techniques for the estimation of crack shape and detection of crack growth in mechanical tests - Buss, Thomas M. (2022)
It is known that cracks grow in materials subject to both mechanical and thermomechanical fatigue. Work has been undertaken to investigate the shapes of cracks in two materials in low cycle fatigue (LCF) and thermomechanical fatigue (TMF) conditions utilising novel Alternating Current Potential Difference (ACPD) and beach marking methods to measure the crack length. This has been added to by the development of a novel beach marking technique which enables the user to define the position and size of marks.